The health of fishes in the urban lagoon os Ilusiones, Tabasco, México - Arias Rodriguez, Lenin (2024)
Water is an important element for almost all biological process and several living organisms like fishes, have their habitat in such a kind of aquatic ecosystems. In the city of Villahermosa, Tabasco Mexico is located the Lagoon of las Ilusiones, which is the habitat of several taxonomic groups like fishes. Unfortunately, the imminent pollution of the water body has been documented and recently evaluated the water well-being by cytological and genetics studies through the use of naïve fish species which are a common. The results of several studies show the terrible conditions of water quality, the effects it manifests on the hematopoietic genetic/cellular components; due to the presence of intracellular damage and various atypical levels of chromosome counts.